A New JPEG Compression Algorithm for Transmission, Processing and Storage of Health Data - Avdin, Yilmaz; Ozkaynak, Fatih (Institute of Electrical and Electronics Engineers Inc., 2024)
This study proposes a new compression algorithm for health data management, which is a derivative of the JPEG algorithm. The proposed method has shown improvement in compression ratio compared to the classical JPEG algorithm, making it a promising solution for the storage and transmission of medical images in PACS systems. The algorithm has been designed with data security in mind and it is planned to integrate it with encryption algorithms in the future. The performance of the proposed algorithm was evaluated through comprehensive testing, and its potential real-world applications were discussed. The results of this study demonstrate the feasibility of the proposed algorithm and suggest that it has the potential to revolutionize the field of health data management. This study provides a roadmap for future work on the proposed algorithm, including its integration with encryption algorithms, performance evaluations, real-world implementation, and continuous improvement. © 2024 IEEE.
6th International Conference on Artificial Intelligence in Information and Communication, ICAIIC 2024 -- 19 February 2024 through 22 February 2024 -- Osaka -- 198237
Keywords: Data compression; DICOM; JPEG; PACS